2021
DOI: 10.1002/jwmg.22122
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Population Growth and Recruitment Rates Across the Range of American Common Eiders

Abstract: Sound management of bird populations rests upon an adequate understanding of their population dynamics. Our study evaluated recruitment and population growth rates of 14 American common eider (Somateria mollissima dresseri) colonies from Labrador, Nova Scotia, Quebec, Canada, and Maine, USA, during various periods between 1970 and 2019. We used Pradel mark‐recapture models to estimate colony‐specific growth rates and the relative contributions of survival and recruitment on growth. We also validated this appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Yet, the presence of transient individuals is very common in many taxa (Oro & Doak, 2020), and the bias they produce in demographic rates may be substantial (Orgeret et al., 2014). The well‐known and widely used original Pradel (1996) temporal symmetry model for CMR data to estimate survival, recruitment and population growth was designed for resident individuals only, but some studies have used it on data with transient individuals, while being aware of the risk of bias in survival and recruitment estimates (Giroux et al., 2021; Rodrigues et al., 2021; Tenan et al., 2014). Another study reported poor model fit (Sasso et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the presence of transient individuals is very common in many taxa (Oro & Doak, 2020), and the bias they produce in demographic rates may be substantial (Orgeret et al., 2014). The well‐known and widely used original Pradel (1996) temporal symmetry model for CMR data to estimate survival, recruitment and population growth was designed for resident individuals only, but some studies have used it on data with transient individuals, while being aware of the risk of bias in survival and recruitment estimates (Giroux et al., 2021; Rodrigues et al., 2021; Tenan et al., 2014). Another study reported poor model fit (Sasso et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For the Pradel model, though, a solution accounting for transients was not available, and this has often been mentioned as a limitation of the Pradel model (Ahrestani et al., 2017; Saracco & Rubenstein, 2020). Many studies using the Pradel model have found the presence of transience, but have not been able to address it properly (Giroux et al., 2021; Rodrigues et al., 2021; Tenan et al., 2014). Using the original Pradel model on data with transients leads to a strong bias in the estimates of survival, seniority (and thus also recruitment) and capture probability (Orgeret et al., 2014), which can lead to poor model fit (Sasso et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is unlikely that subsistence hunting by the residents of Sanikiluaq has prevented an increase in population size. In long-lived birds, such as common eiders, adult survival is the parameter contributing the most to population growth (Giroux et al, 2021;Wilson et al, 2012).…”
Section: Why the Eider Population Has Not Fully Recoveredmentioning
confidence: 99%
“…Factors affecting the reproduction success and overall recruitment of Hudson Bay eiders could have had an impact on population growth and recovery. The adult survival rates of the common eider population are usually high (between 0.8 and 0.95) and relatively stable through time (Giroux et al, 2021;Hario et al, 2009;Wilson et al, 2007;Wood et al, 2021). For eiders, while the adult survival rates contribute the most to population growth (Giroux et al, 2021;Wilson et al, 2012), studies have shown that the recruitment rate is a stronger determinant of the variability in population growth rate (Giroux et al 2021;Hario et Rintala, 2006).…”
Section: Why the Eider Population Has Not Fully Recoveredmentioning
confidence: 99%
See 1 more Smart Citation